2007
DOI: 10.1248/jhs.53.161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psychologic Stress on Peroxidase and Thiocyanate Levels in Human Saliva Detected by Ultraweak Chemiluminescence

Abstract: Saliva sampling has the advantage of being noninvasive and stress free. Based on a recent study, salivary ultraweak chemiluminescence (UCL) is a new biomarker of psychologic stress. However, it is not clear what causes changes in the UCL level and whether the change is biologically significant. We investigated the candidates for salivary UCL induced by psychological stressors and discuss the physiologic function of these candidates. Volunteers completed a questionnaire and then performed the Kraepelin test. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The IgA concentration, Amylase activity, and UCL level were higher in the non-smoking group than smoking group regardless of the Kraepelin test. In our system, OPO catalyzes the oxidation of salivary SCN − by H 2 O 2 to the antimicrobial component hypothiocyanate (OSCN − ) with the emission of UCL as follows (Goi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IgA concentration, Amylase activity, and UCL level were higher in the non-smoking group than smoking group regardless of the Kraepelin test. In our system, OPO catalyzes the oxidation of salivary SCN − by H 2 O 2 to the antimicrobial component hypothiocyanate (OSCN − ) with the emission of UCL as follows (Goi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies we showed that acute stress such as mental arithmetic increased OPO activity and changed several salivary biochemical parameters (Goi et al, 2007). A possible anticarcinogenic role of OPO against the most prevalent and lethal cancer of the oral cavity has been mentioned (Nagler et al, 2002;Zappacosta et al, 1999;Reznick et al, 2003), but whether the response of OPO activity to mental stress changes due to habits such as smoking has scarcely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of cyanide, thiocyanate, ATCA, and cyanide-protein adducts in biological fluids and tissues is useful for forensic, clinical, research, law enforcement, and veterinary purposes. Methods of analysis include spectrophotometry (37,59,62,74,78,81,89,90,93,105,120,130,133,139,141,143,, fluorescence (49,51,89,115,121,132,142,(175)(176)(177)(178)(179)(180)(181), chemiluminescence (77,109), electrochemistry (18, 56, 63-65, 68, 69, 73, 75, 79, 80, 106, 129, 138, 153, 182-197), gas chromatography (GC) (45, 53, 54, 61, 91, 95, 103-105, 107, 108, 111, 113, 114, 117, 119, 121, 125, 126, 128, 131, 135, 137, 152, 198-212), liquid chromatography (LC) (34,40,49,52,66,67,72,92,94,109,110,…”
Section: The Detection Of Cyanide and Its Metabolites In Biological Smentioning
confidence: 99%
“…In addition, we determined that the Kraepelin test, a task requiring a high level of concentration, led to a significant IgA immune response and this response can be estimated from the increase in salivary UCL. We have demonstrated that thiocyanate ions (SCN − ) and peroxidase in the saliva play a key role in salivary UCL . Therefore, salivary UCL may be a new marker by which to measure psychological stress.…”
Section: Introductionmentioning
confidence: 99%